LC-MS identification and preparative HPLC isolation of Frankenia pulverulenta phenolics with antioxidant and neuroprotective capacities in PC12 cell line - Rim Ben Mansour; Megdiche Ksouri Wided; Stéphanie Cluzet; Stéphanie Krisa; Tristan Richard; Riadh Ksouri (Taylor & Francis Group, 2017)
Context: Frankenia pulverulenta L. (Frankeniaceae) is a medicinal species with carminative, analgesic and antiviral properties. However, phytochemical investigations, antioxidant and neuroprotective capacities of this plant remain unclear. Objective: This work assesses the phenolic composition of F. pulverulenta shoot and root and evaluates their antioxidant and neuroprotective capacities. Materials and methods: Successive fractionation of F. pulverulenta shoot and root using 6 solvents were used. Antioxidant capacity of these fractions was assessed through four in vitro tests (DPPH, ABTS, Fe-chelating activity and ORAC). Phenolic identification, purification as well as neuroprotective activity of ethyl acetate (EtOAc) fraction and purified molecules were assessed. Results: Among the tested fractions, EtOAc shoot and root fractions possessed considerable phenolic contents (383 and 374 mg GAE/g E, respectively) because of their important ORAC (821 and 1054 mg of TE/g E), DPPH (586 and 750 mg of TE/g) and ABTS (1453 and 1319 mg of TE/g) results. Moreover, gallic acid, quercetin, quercetin galloyl glucoside, trigalloyl hexoside, procyanidin dimers and sulfated flavonoids were identified by LC-DAD-ESI-MS for the first time in this species. The relevant cytoprotective capacity (at 300 μg/mL) against β-amyloid peptide induced toxicity in PC12 cells of EtOAc fractions were corroborated with the chemical composition. In addition, purified molecules were tested for their ORAC and neuroprotective activity. Quercetin showed the best ORAC value (33.55 mmol TE/g polyphenols); nevertheless, procyanidin dimer exhibited an exceptionally efficient neuroprotective activity (100% of viability at 50 μg/mL). Discussion and conclusions: These findings suggest that this halophyte is a promising source of antioxidant and neuroprotective molecules for pharmaceutical purposes.